Pengaruh Penerapan Sistem Informasi Akuntansi Terhadap Kualitas Output Sistem Informasi Akuntansi dan Sistem Pengendalian Internal Pada Perusahaan BUMN Pengguna Sistem Enterprise Resource Planning (ERP) di Kota Lhokseumawe - Indrayani Indrayani; Maulidahniar Maulidahniar (Program Magister Akuntansi Unsyiah, 2017)
This research conducted to analyze the implementation of Accounting information system that integrated with Enterprise Resource Planning (ERP) system toward output quality of Accounting information system and the influence of Accounting information system that integrated with Enterprise Resource Planning (ERP) system toward the internal control system. The population of this research was all Indonesian State Owned Enterprises in Lhokseumawe city. The sample was taken by applying Purposive sampling technique and there were 5 enterprises that implement Enterprise Resource Planning (ERP) in Lhokseumawe chosen as the sample. The respondents were 30 people. The data used in this research was primary data in form of questionnaire. The method of data analysis was Multiple linear regression using SPSS. The result indicated that the Accounting information system that integrated with Enterprise Resource Planning (ERP) system influenced positively and significantly on the output quality of the Accounting Information system, and the implementation of Accounting information system that integrated with the Enterprise Resource Planning (ERP) system influenced positively and significantly on the internal control system of enterprise.KEYWORDS : Accounting Information System, Enterprise Resource Planning (ERP), Output Quality of Accounting Information System and Internal Control System.